2014
DOI: 10.1007/s12199-014-0380-z
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of physical activity and its relationship to health-related quality of life in patients on chronic hemodialysis

Abstract: Physical activity over 4 METs on non-hemodialysis treatment days might be associated with EQ-5D in patients on chronic hemodialysis, especially in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
41
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 23 publications
9
41
1
2
Order By: Relevance
“…30) [48], an English and Welsh study with a mean of 0. 60 (SD = 0.28) [49], and a Japanese study with a mean of 0.75 (SD = 0.17) [50]. In the present study, we found a significant association between higher QoL and younger age.…”
Section: Discussionsupporting
confidence: 62%
“…30) [48], an English and Welsh study with a mean of 0. 60 (SD = 0.28) [49], and a Japanese study with a mean of 0.75 (SD = 0.17) [50]. In the present study, we found a significant association between higher QoL and younger age.…”
Section: Discussionsupporting
confidence: 62%
“…There have been some reports that have used the EQ‐5D to measure HRQoL in dialysis patients. In one study, the EQ‐5D index score was 0.75 ± 0.17 in Japanese HD patients . In peritoneal dialysis patients, Sakthong et al .…”
Section: Discussionmentioning
confidence: 96%
“…In one study, the EQ-5D index score was 0.75 ± 0.17 in Japanese HD patients. 18 In peritoneal dialysis patients, Sakthong et al 30 reported that the EQ-5D index score was 0.65 ± 0.23 in Taiwan. We evaluated HRQoL using the EQ-5D in HD patients and the index score was 0.704 ± 0.199.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations